A two-degree-of-freedom piezoelectric energy harvester with stoppers for achieving enhanced performance. (December 2018) - Hu, Guobiao; Tang, Lihua; Das, Raj; Marzocca, Pier
Highlights: A two-degree-of-freedom piezoelectric energy harvester with stoppers is proposed. A piecewise linear model is built to describe the proposed impact engaged mechanical system and is solved by using the averaging method. The introduction of the stoppers can widen the operating bandwidth and enhance the power output amplitude. Abstract: Environmental vibrations often exist in a broadband form. To have a robust performance over a wide frequency range, vibration energy harvesters need to be designed to be insensitive to excitation frequencies. In this paper, we propose a novel two-degree-of-freedom (DOF) piezoelectric energy harvester (PEH) with stoppers that introduce nonlinear dynamic interaction between the two DOFs. First, the mechanical model of the 2DOF system with stoppers is developed by emulating the impact behavior as a piecewise linear stiffness and the working principle is explained. Subsequently, the analytical solution of the system with piecewise linear stiffness is derived using the averaging method and the dynamic response of the system is obtained and confirms its wide bandwidth property. Finally, by integrating the mechanical system with a piezoelectric transducer, the energy harvesting performance of the proposed 2DOF PEH with stoppers is numerically evaluated. The open circuit voltage response of the proposed system is compared with that of the conventional linear 2DOF and 1DOF PEHs. A parametric study reveals the effect of the stopper distance on the energy harvesting performance in terms of both the bandwidth and open circuit voltage output. The superiority of the proposed system in terms of both power output and operation bandwidth is demonstrated. Graphical abstract: Image, graphical abstract